DESIGNING THE SPECIAL PILOT ECONOMIC ZONE: AN ALTERNATIVE APPROACH TO REVITALIZE LIVELIHOODS ON PEATLANDS - Budiman, Ibnu; Januar, Rizky; Daeli, Willy; Hapsari, Rahmah D; Sari, Eli NN (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2020)
Peatland restoration projects in tropical countries could prevent environmental disasters such as peat fires. In Indonesia, one of peatland restoration activities is the revitalization of the livelihoods of communities around peatlands. Nevertheless, this activity is still lacking in reducing the environmental pressures from the communities on peatland. We aim to find a comprehensive strategy to design a sustainable bioeconomy on peatlands. This study draws on spatial, qualitative, and quantitative data from the literature, project and policy documents, open-source web application, observations from the field and meetings; and interviews with key stakeholders at national level and three Indonesian provinces. We found that an ecosystem-based special pilot economic zone (SPEZ) is a potential proposal that can provide a framework for a sustainable peatland bioeconomy. We suggests seven phases for planning and implementation of the SPEZ; 1. Preparing its spatial planning to support its legal aspects; 2. Field observation to derive biophysical information of the location and determining peatland suitability; 3. Identifying target group, paludiculture commodities and alternative livelihoods; 4. Analyzing the value chain, market demand and conducting a cost-benefit analysis; 5. Natural capital accounting; 6. Designing social innovation to trigger investment and market chain; and 7. Community engagement. From our study in Riau, South Sumatra, and Central Kalimantan, each of the phase present different challenges and opportunities especially in terms of regulation for land permit, institutional arrangement, market chain for peat products, remuneration of external benefits, and perception and capacity of community for cultivation on peat.